Real life experience confirms sustained response to long-term biologics and switching in ankylosing spondylitis - Laura C. Coates; Lorna Cawkwell; Nora Ng; Alexander N. Bennett; Domini Bryer; Alexander Fraser; Paul Emery; Helena Marzo‐Ortega (2008)
Objective. To investigate the long-term response to biological therapies in AS in a real life clinical setting and to quantify non-response and response to 'switching' therapies in these cases. Methods. All patients prescribed TNF-blocking therapies for AS between 1999 and 2006 were studied. Response was evaluated using Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI) and CRP results. Results. A total of 113 patients (84 males: 29 females, mean age 45 yrs, median disease duration 16 yrs, 87% HLA-B27 positive) were identified. At baseline they had a mean BASDAI of 6.57, BASFI 6.57 and CRP of 31 g/dl. At the end of follow-up, these values had reduced to mean BASDAI of 3.12, BASFI 4.16 and CRP of 7 g/dl. Improvements were sustained for 24 months and beyond with no loss of effect. Only nine patients (8%) suffered side-effects leading to cessation or switching of first-line therapy and non-response occurred in 15 patients (13%) in the long term. Fifteen patients (13%) switched to a second drug and 14 of these (93%) had a significant and sustained response. Outcomes were similar regardless of drug used, duration of disease and HLA-B27 status. Conclusion. Treatment of active AS with TNF blockers according to the British Society of Rheumatology guidelines leads to a sustained response for over 2 yrs with most patients tolerating the drugs well. The rate of non-response is significantly lower than that seen in RA and nearly all of these patients respond well to a second-line agent.